FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT - Marcel Kusuma, Gumulya Sonny (Balance : Jurnal Akuntansi dan Bisnis, 2018)
This study examines the influence of locus of control, performance, organizational commitment onacceptance dysfunctional audit behavior (prematur sign off, underreporting of time, and altering replacing auditprocedure). This research uses convenience sampling technique to select the respondent . Data were collectedthrough a survey on 104 government auditors who work at BPK of Southern Sumatera. Structural Equation Model(SEM) with Partial Least Square (PLS) was applied to analyzed the data. The result of this research indicatepositive influence of locus of control on acceptance dysfunctional audit behavior, negative influence oforganizational commitment on acceptance dysfunctional audit behavior with external locus of control asantecedent, Futhermore, it was found that there were no significant influence on performance on acceptancedysfunctional audit behavior with external locus of control and organizational commitment as antecedent